Vascular infarction by subcutaneous application of tissue factor targeted to tumor vessels with NGR-peptides: activity and toxicity profile - Dreischalück, Johannes; Schwöppe, Christian; Spieker, Tilmann; Kessler, Torsten; Tiemann, Klaus; Liersch, Ruediger; Schliemann, Christoph; Kreuter, Michael; Kolkmeyer, Astrid; Hintelmann, Heike; Mesters, Rolf M.; Berdel, Wolfgang E. (International journal of oncology, 2010)
tTF-NGR consists of the extracellular domain of the (truncated) tissue factor (tTF), a central molecule for coagulation in vivo, and the peptide GNGRAHA (NGR), a ligand of the surface protein aminopeptidase N (CD13). After deamidation of the NGR-peptide moiety, the fusion protein is also a ligand for integrin αvβ3 (CD51/CD61). Both surface proteins are upregulated on endothelial cells of tumor vessels. tTF-NGR showed binding to specific binding sites on endothelial cells in vitro as shown by flow cytometry. Subcutaneous injection of tTF-NGR into athymic mice bearing human HT1080 fibrosarcoma tumors induced tumor growth retardation and delay. Contrast enhanced ultrasound detected a decrease in tumor blood flow in vivo after application of tTF-NGR. Histological analysis of the tumors revealed vascular disruption due to blood pooling and thrombotic occlusion of tumor vessels. Furthermore, a lack of resistance was shown by re-exposure of tumor-bearing mice to tTF-NGR after regrowth following a first cycle of treatment. However, after subcutaneous (s.c.) push injection with therapeutic doses (1-5 mg/kg bw) side effects have been observed, such as skin bleeding and reduced performance. Since lethality started within the therapeutic dose range (LD10 approximately 2 mg/kg bw) no safe therapeutic window could be found. Limiting toxicity was represented by thrombo-embolic events in major organ systems as demonstrated by histology. Thus, subcutaneous injection of tTF-NGR represents an active, but toxic application procedure and compares unfavourably to intravenous infusion.
Gesehen am 16.02.2023